2023
DOI: 10.3390/ani13081279
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Patchouli and Tea Tree Essential Oils against Staphylococci Isolated from Pyoderma in Dogs and Their Synergistic Potential with Gentamicin and Enrofloxacin

Abstract: In this paper, we show the effect of some essential oils (EOs) on staphylococci, including multidrug-resistant strains isolated from pyoderma in dogs. A total of 13 Staphylococcus pseudintermedius and 8 Staphylococcus aureus strains were studied. To assess the sensitivity of each strain to the antimicrobial agents, two commercial EOs from patchouli (Pogostemon cablin; PcEO) and tea tree (Melaleuca alternifolia; MaEO) as well as two antibiotics (gentamicin and enrofloxacin) were used. The minimum inhibitory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
6
0
1
Order By: Relevance
“…For this purpose, the biological activity of other major and minor components of lavender essential oils should be tested in analogous conditions to identify the remaining active compounds. Some authors have shown synergistic effects with gentamicin for other essential oils against Gram-positive and Gram-negative bacteria [1,44,[49][50][51]. This was confirmed in our previous study on commercial lavender essential oil [7] and the currently studied oils isolated from different cultivars and morphological parts of lavender, whose combinations with gentamicin have not yet been examined.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For this purpose, the biological activity of other major and minor components of lavender essential oils should be tested in analogous conditions to identify the remaining active compounds. Some authors have shown synergistic effects with gentamicin for other essential oils against Gram-positive and Gram-negative bacteria [1,44,[49][50][51]. This was confirmed in our previous study on commercial lavender essential oil [7] and the currently studied oils isolated from different cultivars and morphological parts of lavender, whose combinations with gentamicin have not yet been examined.…”
Section: Discussionsupporting
confidence: 73%
“…The overall concept of antimicrobial synergy is based on the principle that the combination of two or more antimicrobial agents (even in lower amounts) may enhance their efficacy. This is manifested, for example, due to their hydrophobicity, by reaction with lipids present in the bacterial cell membrane (e.g., destroying cell structures or increasing the permeability of the main component), a reduction in the required dose of the active substance or reduced antimicrobial resistance [44]. The biosynthesis of secondary metabolites and their proportion in essential oils vary due to environmental factors, such as seasonal variation, light availability, vegetation stage, presence of additional commensal microorganisms as well as nature of soil (e.g., pH) [42].…”
Section: Discussionmentioning
confidence: 99%
“…Further researches are necessary to comprehensively comprehend the mechanisms of EOs and their suitable use in clinical settings [ 18 , 19 ]. In recent years, various in vivo and in vitro investigations have been conducted focusing on the efficiency of several EOs against the etiological agents of pyoderma in dogs [ 15 , 20 , 21 , 22 ]. Many EOs may be used to treat various skin disorders; however, due to their bioactive chemical components, some are particularly efficient against Gram-positive and Gram-negative bacteria [ 23 ], in particular those with significant percentages of thymol and carvacrol have extraordinary membrane-damaging action in bacteria [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of antibiotics was a medical advancement, but bacterial resistance accelerated by genetic mutations resulted in rapid resistance. Meanwhile, a new class of antibiotics had not been developed for over three decades [1]. Research on antimicrobial substances using natural resources has become a serious discussion by researchers [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that EOs from dissimilar plants and plant parts are quite different in chemical compounds and antimicrobial characteristics [16,17]. Interest in EOs and their use is steadily increasing, especially in the medical, cosmetic, and culinary industries [1]. Steam distillation can obtain EOs from different plant materials (leaves, buds, fruits, flowers, herbs, branches, bark, wood, roots, and seeds).…”
Section: Introductionmentioning
confidence: 99%